2007
DOI: 10.1590/s1413-86702007000100024
|View full text |Cite
|
Sign up to set email alerts
|

Angioinvasive pulmonary aspergillosis after allogeneic bone marrow transplantation: clinical and high-resolution computed tomography findings in 12 cases

Abstract: The aim of this study was to present the clinical and high-resolution CT scan findings of angioinvasive pulmonary aspergillosis (APA) in 12 patients who underwent allogeneic bone marrow transplantation (BMT). The CT scans were reviewed by three chest radiologists who assessed the pattern and distribution of findings by consent. There were 7 (58%) female and 5 (42%) male patients, with aging between 5 and 50 years (average of 26 years). All patients were submitted to BMT for the treatment of hematological condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In our study, the halo sign was identified in 25% of the patients that had a CT scan (4/16). Gasparetto et al [14], in a review of 12 cases, identified the halo sign in 5 of 12 patients (41%); bilateral and asymmetric distribution of lesions was the dominant pattern (66%). When we compared the pediatric and adult groups, we did not find significant differences (p=0.63, chi-square test with Yates correction).…”
Section: Findingmentioning
confidence: 99%
“…In our study, the halo sign was identified in 25% of the patients that had a CT scan (4/16). Gasparetto et al [14], in a review of 12 cases, identified the halo sign in 5 of 12 patients (41%); bilateral and asymmetric distribution of lesions was the dominant pattern (66%). When we compared the pediatric and adult groups, we did not find significant differences (p=0.63, chi-square test with Yates correction).…”
Section: Findingmentioning
confidence: 99%
“…16). In later stages, CT might show areas of necrotic tissue and pulmonary sequestration within the surrounding parenchyma, resulting in the air crescent sign [31].…”
Section: Fungal Pneumoniamentioning
confidence: 99%